Sunitinib cause delayed complete response on metastatic RCC and extensive IVC thrombus, but not to the kidney tumor: a case report and review of literature. Issue 11 (11th November 2019) - Beltagy, Ahmad; Ismail, Asmaa; Elmansy, Hazem; Shahrour, Walid; Prowse, Owen; Kotb, Ahmed
Abstract: The role of cytoreductive nephrectomy for metastatic renal cell carcinoma (RCC) is currently debated, with the advancements in target therapy development. The aim of our work was to present an interesting case report with mini review to describe the important role of cytoreductive nephrectomy for kidney cancer control that failed to respond well to Sutent, in spite of good response for all metastases. Medline review of related English publication was conducted and included to the study. RCC response to Sutent is inferior to the response of its metastases. Cytoreductive nephrectomy still plays an important role in metastatic RCC and may be an integral part for cancer control, in properly selected patients.